Interpreting Lee’s Rose: Symbolism as a Bridge between Memory and Identity - Sapkota, Tika Ram (Journal of Interdisciplinary Studies, 2026)
Employing the qualitative text-centered approach with thematic and interpretative structured analytical design, this study has examined Lee’s (1986) poetic collection, Rose examining “rose” as a complex, multi-layered symbol to bridge present reality with the memory of the past. The paper aims to seek out how the poet reflects his bicultural experiences in a diverse cultural background by using different symbols and imageries. The research has addressed the drawback of conventional, romanticized judgement of the flower creating a gap by inspecting Lee’s use of images to navigate the trauma of diasporic life. Close reading of the text’s structural design has indicated that the rose functions as “doomed profane flower” and linguistic homonym for “rising” which allows the object to transition from symbol of decay into a mechanism for spiritual revival. The implication of these symbols elevates the domestic elements to the sacred sensory for the “thousand-mile- sadness” of displacement. The study concludes that symbolism in the poem serves as profound tool to transform the fragility of life being in diasporic nationality into a resilient bridge between the finite reality of loss and the eternal nature of love.